Islamic tourism in Southeast Asia: The concept and its implementation - Wahyono, Zubaidi; Abdul Razak, Mohd Abbas (2019)
Tourism has now become an important source of revenue for many countries in the world. The spillover from this booming and lucrative industry impacts positively the other sectors of the national economy in those countries. This situation is not only true in the advanced countries of the world, but also in the Muslim world. In this present study on Islamic tourism the researchers intend to investigate the definition, destination, purpose and ethical issues related to Islamic tourism. Very particularly, the study will focus on the situation in three of the Muslim countries situated in the region of Southeast Asia; namely Malaysia, Indonesia and Brunei. Driven by the passion to study on Islamic tourism, the researchers are interested to know the guiding principles set in these countries in contrast to others in the region. Apart from the crux of the investigation, on the peripheral, this study will also look into the topic of tourism from the Islamic ethical dimension, mainly referring to the Qur’an and Sunnah. As a qualitative study, the researchers will employ the library research approach in collecting the pertinent data related to the study. By using the textual-analysis method they will scrutinize data collected from online and print materials. It is hoped that this modest research can be a contribution in advancing Islamic tourism in the Malay Archipelago and elsewhere in the world.